Pengaruh Pemberian Akupresur oleh Anggota Keluarga terhadap Tingkat Nyeri Pasien Nyeri Kepala (Chephalgia) di Kota Padang Panjang - Rika Roza; Budhi Mulyadi; Yonrizal Nurdin; Mahathir Mahathir (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Chephalgia is grievance that is often felt like discomfort in head, Chephalgia can bother activity and productivity. One of complementary therapy that can reduce Chephalgia is acupressure. This study aims to determine the effect of acupressure by family member on pain level of Chephalgia patient in Padang Panjang conducted february-September 2019. The study is an experimental design and a pretest-posttest with control group design with 116 of samples and it uses simple random sampling. Different levels of pain before and after the administration of acupressure by family members used the Wilcoxon test. Whereas to see the comparison of the intervention group and the control group used to test two different groups used the mann withney test.. Satistic test result get p value = 0.0000 that means there is significant effect between before and after acupressure on intervention group, but there is no significant effect on control group get p value = 0,771. This therapy acupressure is recomended for solving Chephalgia, it means that we can give nursing complementary therapy for minimizingC.